The Process Of Resolving Compensation Claims Against Victims Of Defamation Through Social Media - Silitonga, Hartati; Esther, July; Nababan, Roida (Indonesian Journal of Law and Justice, 2025)
Defamation through social media has become a significant problem in the digital era. This study aims to analyze the process of resolving compensation claims due to defamation and the form of legal protection based on the Civil Code. The research uses a normative juridical method with a qualitative approach, referring to laws and regulations, court decisions, and legal doctrine. The results show that dispute resolution can be done through litigation and non-litigation channels. Litigation includes formal stages such as filing a lawsuit, mediation, proof, and a judge's decision based on Articles 1365 and 1372 of the Civil Code. Meanwhile, non-litigation channels such as negotiation and mediation emphasize peaceful settlement. Legal protection for victims includes material and immaterial damages, the amount of which is determined based on the perpetrator's guilt, causal relationship, and strong evidence. Although restitution is generally in the form of money, other forms of restitution are also possible. This study emphasizes the importance of a fair and proportional legal approach to safeguard victims' rights and prevent abuse of freedom of expression on social media.